Monetary reforms in the Carolingian era: Historical study (754-1173) (Abhat Journal, 2025)
This study looks at monetary reforms in the Carolingian era in terms of the rulers’ interest in coinage, the choice of mints, and the most important reforms that occurred in previous currencies and the cancellation of some of them particularly what happened in the era of Charlemagne and his son Louis the Pious. The study also looks at the changes in the currency in terms of the metal used and the quality and purity of the currency. The study also aims to study the impact of money on the commercial aspect, and to determine the eras to which its minting dates back. It also describes the fluctuations that occurred in its value, and counterfeiting was one of the factors affecting it. Many rulers issued strict decrees to address these problems, with penalties ranging from imprisonment, amputation of the hand, and payment of fines.
Keywords: Monetary; Coins; Charlemagne; Carolingians; Minting